Vibration Analysis of Multilayer Stepped Cross-Sectional Carbon Nanotubes - Yildiz, Yunus Onur; Sen, Murat; Yigid, Osman; Huseyinoglu, Mesut; Kara, Sertac Emre (Mdpi, 2025)
This study comprehensively investigates the dynamic vibration behavior of multilayer carbon nanotubes with stepped cross-sectional geometries under various boundary conditions, which is crucial for their advanced engineering applications. The methodology integrates classical molecular dynamics simulations to determine the bending stiffness of single-walled and multi-walled atomistic structures, which are subsequently utilized in the Euler-Bernoulli beam theory based on nonlocal elasticity for vibration analysis. The research focuses on elucidating the influence of the mu/L ratio (a key length parameter) and different support conditions on the natural frequencies and mode shapes of these nanostructures. Key findings reveal that the cross-sectional geometry significantly impacts the vibrational characteristics. A consistent trend observed across all examined boundary conditions is a decrease in natural frequencies as the mu/L ratio increases, indicating that increased free length or reduced fixed length leads to lower stiffness and, consequently, reduced natural frequencies. The study presents Frequency Response Functions (FRFs) and the first four mode shapes, which visually confirm these dynamic characteristics. Graphical representations further reinforce the sensitivity of natural frequencies to both the mu/L ratio and support conditions. The systematic analysis presented in this work provides vital data for predicting resonance phenomena, optimizing structural stability, and enabling precise control over the vibrational response of these advanced nanomaterials in diverse engineering applications.
Keywords: modal analysis; molecular dynamics; natural frequency; carbon nanotube; multilayer carbon nanotubes